Association Between Performance on Timed Up and Go Subtasks and Mild Cognitive Impairment: Further Insights into the Links Between Cognitive and Motor Function. Issue 4 (17th March 2014) - Mirelman, Anat; Weiss, Aner; Buchman, Aron S.; Bennett, David A.; Giladi, Nir; Hausdorff, Jefferey M.
<x xml:space="preserve">Abstract</x> Objectives To assess whether different Timed Up and Go (TUG) subtasks are affected differently in older adults with mild cognitive impairment (MCI) and are specific to different cognitive abilities. Design Cross‐sectional. Setting Community and home. Participants Older adults without dementia (N = 347; mean age 83.6 ± 3.5, 75% female, 19.3% with MCI) participating in the Rush Memory and Aging Project. Measurements Subjects wore a small, light‐weight sensor that measured acceleration and angular velocity while they performed the instrumented TUG (iTUG). Measures of iTUG were derived from four subtasks (walking, turning, sit‐to‐stand, stand‐to‐sit) and compared between participants with MCI and those with no cognitive impairment. Results Participants with no cognitive impairment and those with MCI did not differ in age (P = .90), sex (P = .80), years of education (P = .48) or time to complete the TUG (no cognitive impairment 7.6 ± 3.7 seconds; MCI 8.4 ± 3.7 seconds; P = .12). Participants with MCI had less walking consistency (P = .009), smaller pitch range during transitions (P = .005), lower angular velocity during turning (P = .04) and required more time to complete the turn‐to‐walk (P = .04). Gait consistency was correlated with perceptual speed (P = .01), and turning was correlated with perceptual speed (P = .02) and visual‐spatial abilities (P = .049). Conclusion Mild cognitive impairment is associated with impaired performance on iTUG subtasks that cannot be identified when simply measuring overall duration of performance. Distinctive iTUG tasks were related to particular cognitive domains, demonstrating the specificity of motor–cognitive interactions. Using a single sensor worn on the body for quantification of mobility may facilitate understanding of late‐life gait impairments and their interrelationship with cognitive decline.